2015
DOI: 10.1007/s11589-015-0111-6
|View full text |Cite
|
Sign up to set email alerts
|

Satellite detection of IR precursors using bi-angular advanced along-track scanning radiometer data: a case study of Yushu earthquake

Abstract: The paper has developed and proposed a synthesis analysis method based on the robust satellite data analysis technique (RST) to detect seismic anomalies within the bi-angular advanced along-track scanning radiometer (AATSR) gridded brightness temperature (BT) data based on spatial/temporal continuity analysis. The proposed methods have been applied to analyze the Yushu (Qinghai, China) earthquake occurred on 14th April 2010, and a full AATSR data-set of 8 years data from March 2003 to May 2010 with longitude f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Application of particularly sophisticated techniques is mandatory to identify the anomalous signal in the TIR data. For instance, [ 119 , 120 , 121 , 122 ] propose some robust satellite techniques that take into proper account the past behavior of the signal under investigation: the typical seasonal and yearly background is computed and statistically significant deviation from it may represent the thermal anomaly. [ 123 ] focused the attention on the air-quality data as possible indicators of an impending EQ: these authors found a staggering increase in ambient SO 2 concentrations by more than one order of magnitude across Taiwan several hours prior to two (M6.8 and M7.2) significant EQs in the island.…”
Section: Lithosphere-atmosphere-ionosphere Coupling (Laic)mentioning
confidence: 99%
“…Application of particularly sophisticated techniques is mandatory to identify the anomalous signal in the TIR data. For instance, [ 119 , 120 , 121 , 122 ] propose some robust satellite techniques that take into proper account the past behavior of the signal under investigation: the typical seasonal and yearly background is computed and statistically significant deviation from it may represent the thermal anomaly. [ 123 ] focused the attention on the air-quality data as possible indicators of an impending EQ: these authors found a staggering increase in ambient SO 2 concentrations by more than one order of magnitude across Taiwan several hours prior to two (M6.8 and M7.2) significant EQs in the island.…”
Section: Lithosphere-atmosphere-ionosphere Coupling (Laic)mentioning
confidence: 99%
“…Experts and scholars in the field of engineering seismology have obtained stable spectral curves using the microtremor H/V spectral ratio method, which can provide a more accurate resonance frequency for the site [12]. By converting frequencies into periods, they can determine site classifications, divide geotechnical types, and calculate the overburden thickness [13]. Compared with the borehole exploration method, the microtremor H/V spectral ratio method has the characteristics of rapid study of the site, and it has the advantages of simple operation, economic efficiency, environmental friendliness, and less limited conditions of the site [14].…”
Section: Introductionmentioning
confidence: 99%